2017
DOI: 10.1177/0306624x17691533
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of the Effects of Work Environment Variables on Job Satisfaction Among Chinese Prison Staff

Abstract: Job satisfaction has been linked to many positive outcomes, such as greater work performance, increased organizational commitment, reduced job burnout, decreased absenteeism, and lower turnover intent/turnover. A substantial body of research has examined how work environment variables are linked to job satisfaction among U.S. correctional staff; far less research has examined prison staff in non-Western nations, especially China. Using survey data collected from two prisons in Guangzhou, China, this study inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 66 publications
1
32
0
Order By: Relevance
“…For the views of the community-based crime opportunity prevention model, all three significant predictors were institutional factors. The findings that, relative to individual characteristics, institutional or organizational factors have stronger impacts on offenders’ attitudes are also found in other correctional studies in China (Jiang, Jin et al, 2016; Jiang, Lambert, Liu, & Zhang, 2018; Jiang, Lambert, Liu, Kelley et al, 2018; Jiang, Lambert, Zhang et al, 2018) and the United States (Lambert, 2004; Lambert & Hogan, 2009).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…For the views of the community-based crime opportunity prevention model, all three significant predictors were institutional factors. The findings that, relative to individual characteristics, institutional or organizational factors have stronger impacts on offenders’ attitudes are also found in other correctional studies in China (Jiang, Jin et al, 2016; Jiang, Lambert, Liu, & Zhang, 2018; Jiang, Lambert, Liu, Kelley et al, 2018; Jiang, Lambert, Zhang et al, 2018) and the United States (Lambert, 2004; Lambert & Hogan, 2009).…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies have established that institutional factors are important predictors of officers’ attitudes toward organizations and jobs in community corrections (Jiang, Jin et al, 2016; Jiang, Lambert, Zhang et al, 2018; Jiang, Lambert et al, 2016; Jiang et al, 2015) and prison (Jiang, Lambert, Liu, & Zhang, 2018; Jiang, Lambert, Lui, Kelley et al, 2018; Liu, Lambert, Jiang, & Zhang, 2017) in China and prison in the United States (Lambert, 2004; Lambert & Hogan, 2009). Attitude studies among Chinese community corrections officers also showed that one type of work attitude often affected another work attitude.…”
Section: Institutional Factorsmentioning
confidence: 99%
“…While most Chinese government employees work eight hours a day, prison staff work 12hour shifts and may be required to work overtime or work on days off if the need arises, such as emergencies (Wang & Kong, 2006;Xing, 2014). As found in many United States prisons, Chinese inmates are generally less educated, are more antisocial, and have higher rates of mental health and drug problems than the general population (Jiang, Lambert, Liu, & Zhang, 2017). Chinese prisons use a military-like hierarchical ranking system for staff; however, unlike United States prisons, there is not a clear division of labor by prison in Chinese prisons, such as custody, educational, vocational, treatment and support.…”
Section: Brief Overview Of Chinese Prisonsmentioning
confidence: 99%
“…Job satisfaction has significant effects on organizational outcomes such as patient care quality (Boamah, Read, & Spence Laschinger, 2017), work performance, organizational commitment, burnout and turnover (Jiang et al, 2018). The research in nurses' job satisfaction have shown that work environment variables have stronger relationships with job satisfaction: for instance, poor work environments related with inadequate staffing levels decrease job satisfaction and the quality of the care provided in hospital settings (Lu, Ruan, Xing, & Hu, 2015).…”
Section: Problem Statementmentioning
confidence: 99%
“…Job satisfaction refers, essentially, to the degree that a collaborator likes his job (Jiang, Lambert, Liu, & Zhang, 2018). Temesgen, Aycheh, & Leshargie (2018) states that it can been seen as the worker´s emotional response to different job-related factors resulting in finding pleasure, comfort, confidence, rewards, personal growth and various positive opportunities, including upward mobility, recognition, and appraisal done on a merit pattern with monetary value as compensation.…”
Section: Introductionmentioning
confidence: 99%